Proses Penalaran Abduktif Dalam Menyelesaikan Masalah Aljabar - Zahroh, Alfiatuz; Sadieda, Lisanul Uswah; Lailiyah, Siti; Bahasa Indonesia, Bahasa Indonesia (Program Studi Pendidikan Matematika Universitas Muhammadiyah Sukabumi (UMMI), 2025)
This article aims to describe the abductive reasoning process in solving algebra. In this research, the literature study method was used. Based on the results of studies that have been conducted, abductive reasoning helps students make creative and flexible guesses, especially when the solution is not clear at the start. By applying abductive reasoning to solve algebra problems, students are directed to recognize abductive problems, identify various solutions then select the best solution, and assimilate. The solution found must be re-evaluated because there is no guarantee that the solution obtained from the abductive reasoning process is correct.